2019
DOI: 10.1590/1678-6971/eramg190135
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Companies and Cultural Orientation to Innovation: A Multilevel Study

Abstract: Purpose: Test the influence of cultural orientation to innovation on the number of innovations measured in Brazilian companies. Originality/value: The study uses an approach that has not yet been explored in the area, the multilevel analysis. Design/methodology/approach: Five cultural orientation factors for innovation were considered: Rituals and Stories; Innovation strategies; Symbols and Heroes; Autonomy; and Standards and Communication. Innovation has been subdivided into four types: product, service, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
(145 reference statements)
0
2
0
4
Order By: Relevance
“…Ante ello, se infiere que el desarrollo de productos afines a las necesidades del mercado, obliga a considerar un acercamiento con los clientes para poder innovar en las estrategias de mercadotecnia (Francischeto y Neiva, 2019), además de precisar y modernizar (Tulchynska et al, 2021) la colocación del producto más adecuado en los clientes.…”
Section: Estos Resultados Permitieron Comprender Los Argumentos De Th...unclassified
See 2 more Smart Citations
“…Ante ello, se infiere que el desarrollo de productos afines a las necesidades del mercado, obliga a considerar un acercamiento con los clientes para poder innovar en las estrategias de mercadotecnia (Francischeto y Neiva, 2019), además de precisar y modernizar (Tulchynska et al, 2021) la colocación del producto más adecuado en los clientes.…”
Section: Estos Resultados Permitieron Comprender Los Argumentos De Th...unclassified
“…Al respecto, Majied, Abdulhabib y Bani (2020), argumentan que el entorno competitivo induce a las organizaciones a innovar en sus productos, procesos y servicios para obtener una ventaja competitiva que agregue valor para los clientes. Por lo tanto, la innovación es una herramienta esencial para la supervivencia y éxito de una organización (Francischeto y Neiva, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For large companies, it is difficult to change how processes and practices are executed because they were built on successful strategies that worked well enough in the past (CORSI; PRENCIPE; CAPRIOTTI, 2019). The structure, processes, and culture of the established company may be so rigid and bureaucratic that it makes it difficult to innovate Renata Simões Guimarães e Borges, Gilvan Augusto Silva (FRANCISCHETO;NEIVA, 2019). The interviews of Kim, Bae and Bruton (2012) revealed that some executives of established companies themselves admitted that incubation programs run internally, without the interface of external incubators, are more likely to fail because of their cultural rigidness.…”
Section: Steering By the Incubation Programmentioning
confidence: 99%
“…Um dos objetivos centrais da teoria de criação do conhecimento organizacional é identificar as condições ou o contexto capacitante que estimula a geração de novos conhecimentos e a inovação. Página | 5 processo de criação do conhecimento e fornecem as bases para os indivíduos interpretarem situações e problemas, dando a elas significados (Kaplan, 2017;Francischeto, & Neiva, 2019).…”
Section: Intervenientesunclassified